Patient Expectations and Satisfaction When Using a Student-Run Health Clinic - Stephanie Mischell; Nikhil Yegya-Raman; Kiersten Frenchu; Karen Lin (Journal of Student-Run Clinics, 2017)
Background: Promise Clinic, a student-run continuity-based free health clinic affiliated with Rutgers Robert Wood Johnson Medical School, serves the uninsured and low-income population in New Brunswick, New Jersey. Though it has been operating for over ten years, Promise Clinic does not yet have a formalized system for evaluating quality of care from a patient’s perspective. The purpose of this study was to investigate patient satisfaction and expectations at Promise Clinic. Methods: Over a two-month span, we interviewed 21 patients at Promise Clinic. The interview addressed a variety of factors, including patient satisfaction with student doctors, health education and awareness, and understanding of and access to community health options. Furthermore, we elicited open-ended feedback from patients, allowing them to express opinions regarding their healthcare and reasons for attending Promise Clinic over other low-income healthcare providers. Results: We found that while patients were highly satisfied with their overall experience and student doctor teams, there were some concerns about wait times, the timing of clinic, and student doctor preparedness. Patient health education was strong in many, but not all, areas. Of eligible patients, 40.0% reported receiving regular cancer screenings and 33.3% were unaware of other healthcare options. Conclusions: Overall, this study provides a patient-centered assessment of the clinic. Insight obtained has helped medical students and faculty administrators at Promise Clinic address chief patient concerns and improve upon the patient experience. We hope that patient interviews will continue to be a part of quality improvement processes at Promise Clinic and other similar clinics.